A citizen engagement approach to water advocacy: experiences from "eXXpedition Great Lakes". (2nd July 2016) - Pate, J.A.; McKinnon, E.E
ABSTRACT: The Great Lakes are a group of interconnected lakes located on the Canada–United States border. Lake Superior, Michigan, Huron, Erie and Ontario form the largest group of freshwater lakes on Earth, and contain around 21% of the world's surface fresh water by volume. These lakes suffer from considerable microplastic contamination. Despite this awareness, citizens around the lakes struggle to take action. With over 80% of plastic debris in the world's water bodies being contributed from land, the solutions for eliminating microplastics have to come from changes in consumer behaviour and by stopping contamination at the source. "eXXpedition Great Lakes 2016″ was designed as a one-day mass engagement event to bring the science of microplastics to citizens across the region, allowing them to experience first hand the presence and impact of this pollution. Volunteers collected water samples and conducted shoreline clean-ups on the Great Lakes and connecting waterways. Sailing vessels led by female scientists specialising in plastic pollution, human and environmental health were also launched from key cities in both Canada and the United States. The approach was to utilise the power of citizen engagement to promote clean-water advocacy and action in North America. By experiencing the issue of microplastics pollution first hand, it was hoped that participants would feel an increased sense of responsibility and consider protection of the environment as their duty, which would hopefully lead to changes in consumer behaviour. This paper shares the experiences during the event.